THE IMPLEMENTATION OF GEOGRAPHY LEARNING THROUGH THE CONCEPT OF GREEN BUILDING IN GRADE XI SOCIAL STUDIES STUDENTS OF SMAN 3 JEMBER TOWARDS ENERGY-SAVING ATTITUDES (WATER AND ELECTRICITY) - Umi Fauziah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
The Intergovernmental Panel on Climate Change (IPCC) warns that there are only 12 years left or until 2030 to prevent extreme climate disasters that occur due to global warming (Global Warming). One of the triggers for global warming is air pollution triggered by the large emissions of global greenhouse gases (GHGs). Efforts to reduce the amount of greenhouse emissions emitted by large-scale buildings or civil buildings are to apply the Green Building concept. The research design in this study is survey research with the expost facto method. The research instrument uses tests and questionnaires to answer the research hypothesis, with data analysis techniques using the Paired Sample T Test test to measure the impact of the green building concept on learning outcomes and a simple linear regression correlation coefficient to measure the effect of green building concept learning on energy-saving attitudes. From the results of the Paired Sample t test, a value of t = 0.525 was obtained, because the value of t>0.05 then the Ha hypothesis can be accepted, so there is a significant influence on learning using the green building concept with the learning outcomes of class XI students specializing in social studies at SMAN 3 Jember. As for the results of the simple linear regression correlation coefficient test, the results of which there was a significant influence on learning the green building concept with a water and electricity energy-saving attitude of class XI students specializing in social studies at SMAN 3 Jember.